Ackee Growing in the Florida Home Landscape: HS1128/HS378, 1/2008 - Crane, Jonathan H.; Balerdi, Carlos F. (EDIS, 2008)
HS1128, an 8-page illustrated fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides information about this fruit which is a common ingredient in Jamaican cooking, but which is not recommended for home landscape use due to the fact that the fruit is extremely poisonous when it is under-developed or over-ripe. Includes references, cultural calendar, fertilizer recommendations and nutrient values. Published by the UF Department of Horticultural Sciences, January 2008. HS1128/HS378: Ackee Growing in the Florida Home Landscape (ufl.edu)